"Snowplow" injection front effects. Issue 10 (29th October 2013) - Moore, T. E.; Chandler, M. O.; Buzulukova, N.; Collinson, G. A.; Kepko, E. L.; Garcia‐Sage, K. S.; Henderson, M. G.; Sitnov, M. I.
Abstract [1] As the Polar spacecraft apogee precessed through the magnetic equator in 2001, Polar encountered numerous substorm events in the region between geosynchronous orbit and 10 RE geocentric distance; most of them in the plasma sheet boundary layers. Of these, a small number was recorded near the neutral sheet in the evening sector. Polar/Thermal Ion Dynamics Experiment provides a unique perspective on the lowest‐energy ion plasma, showing that these events exhibited a damped wavelike character, initiated by a burst of radially outward flow transverse to the local magnetic field at 80 km/s. They then exhibit strongly damped cycles of inward/outward flow with a period of several minutes. After one or two cycles, they culminated in a hot plasma electron and ion injection, quite similar to those observed at geosynchronous orbit. Cold plasmaspheric plasmas comprise the outward flow cycles, while the inward flow cycles contain counterstreaming field‐parallel polar wind‐like flows. The observed wavelike structure, preceding the arrival of an earthward moving substorm injection front, suggests an outward displacement driven by the inward motion at local times closer to midnight, that is, a "snowplow" effect. The damped in/out flows are consistent with interchange oscillations driven by the arrival at the observed local time by an injection originating at greater radius and local time.